Bond-Graph Model Based Stepper Motor Output Characteristics Simulation Implemented in LabVIEW Environment - Molnár, Zsolt; Husi, Géza (Recent innovations in mechatronics, 2024)
In the industry, simulations are of great importance. They enable measurements to be made in different conditions about a virtual device, which are highly comparable to measurements made in a real life scenarios. Because of their wide range of usage in lower power drive systems, where precision and simplicity is a must, the subject of study is a permanent magnet stepper motor. For precise positioning purposes, it is essential to know the positioning behaviour of these devices. The model construction process involved an intermediate step, which consisted of creating the Bond-Graph of the motor based on pre-defined models available in the literature in this field. In the next step, the Bond-Graph model was converted to a block diagram of the motor. This permitted the direct implementation of the motor model in LabVIEW visual programming environment. The preliminary steps allows us to check and confirm the functionality and correctness of the model. This article covers in detail the model conversion and implementation steps of the simulation. At the end, the functionality of the simulation was tested. In the industry, simulations are of great importance. They enable measurements to be made in different conditions about a virtual device, which are highly comparable to measurements made in a real life scenarios. Because of their wide range of usage in lower power drive systems, where precision and simplicity is a must, the subject of study is a permanent magnet stepper motor. For precise positioning purposes, it is essential to know the positioning behaviour of these devices. The model construction process involved an intermediate step, which consisted of creating the Bond-Graph of the motor based on pre-defined models available in the literature in this field. In the next step, the Bond-Graph model was converted to a block diagram of the motor. This permitted the direct implementation of the motor model in LabVIEW visual programming environment. The preliminary steps allows us to check and confirm the functionality and correctness of the model. This article covers in detail the model conversion and implementation steps of the simulation. At the end, the functionality of the simulation was tested.